Print Media and Cultural Identity of Santri: Responses of the Pesantren's Young Leaders in Indonesia - Ismah, Nor (DINIKA : Academic Journal of Islamic Studies, 2016)
The development of Islamic print media that targets youth as readers has challenged pesantren for selecting appropriate reading materials for students according to its values and tradition. This paper aims to examine the dynamics life of pesantren as “fortress for the defense of the Islamic community” in dealing with influences coming from outside of pesantren. Analyzing the responses of young leaders of pesantren to print media (books, novels, and magazines) containing Islamic values and symbols, and targeting Muslim teenagers as their readers and consumers, with focusing on how these media might influence the establishment of the cultural identity of santri. My paper will answer two main questions: how do the young pesantren leaders respond on the emergence of many novels and magazines that come into the pesantren? What are the rules and regulations they introduce to preserve the cultural identity of santri? In dealing with the challenge of print media, most of the pesantren where these young pesantren leaders live have an “exception” regarding book materials as an attempt to form and protect the cultural identity of santri.